Enhancing star fruit shelf life using edible coatings from babassu starch and oil with plasticizers - Rodrigo Anacleto Pinto; Romerson Ambrósio da Silva; Gislane Romano Mendonça; Virginia Kelly Gonçalves Abreu; Tatiana de Oliveira Lemos; Djany Souza Silva; Daniela Souza Ferreira; Ana Lúcia Fernandes Pereira (Pesquisa Agropecuária Brasileira)
Abstract The objective of this work was to determine the effect of edible coatings made with babassu (Orbignya phalerata) starch and oil, combined with different plasticizers, on the shelf life of star fruit (Averrhoa carambola). The experimental design was completely randomized, in a 5×6 factorial arrangement, with five treatments and six storage periods, with ten replicates per treatment in each storage period. The fruits were stored for 20 days at 10°C and a relative humidity of 65-70%. Five treatments were evaluated: four coated ones (with starch+glycerol, starch+mannitol, starch+oil+glycerol, and starch+oil+mannitol) and one uncoated (control). The studied variables were: mass loss, pH, titratable acidity, soluble solids, ascorbic acid, and color. Mass loss, pH, soluble solids, redness, and yellowness increased linearly during storage, whereas titratable acidity, ascorbic acid, and luminosity decreased linearly. The starch+mannitol treatment stood out, presenting the highest luminosity and the best interaction with babassu oil, which reduced fruit yellowness. However, this interaction caused a lower adherence of the plasticizer to the peel of the fruit, not slowing its ripening down. The use of the starch+mannitol coating reduced mass loss and polysaccharide conversion into soluble sugars. Therefore, this treatment is a promising eco-friendly technique for an improved postharvest storage of star fruit.